Book Reviews (Journal of Finance, 1993)
Book reviewed in this article: Investor Response to Management Decisions: A Research‐based Analysis of Actions and Effects . By RICHARD M. ALTMAN. New York: Quorum Books, 1992. Pp. xiv + 375. Dynamic Asset Pricing Theory . By DARRELL DUFFIE. Princeton: Princeton University Press, 1992. Pp. xvi + 299. Finance in a Theory of the Business Cycle . By ROBERT E. KRAINER. Cambridge: Blackwell Publishers, 1992. Pp. xx + 245. The swaps Market . By JOHN F. MARSHALL and KENNETH R. KAPNER. Miami: Kolb Publishing, 2nd ed., 1993. Pp. 258. Chaos and Order in the Capital Markets: A New View of Cycles, Prices, and Market Volatility . By EDGAR E. PETERS. New York: John Wiley, 1991. Pp. xii + 240. Profit‐Making Speculation in Foreign Exchange Markets . By PATCHARA SURAJARAS and RICHARD J. SWEENEY. Boulder, Colorado: Westview Press, 1992. Pp. xiv + 280.